The importance of providing safety training for ship crews based on STCW - Dipta, I. W. Gede; Giyas, M.; Azmi, M. Aidil; Wanadi, Adil (Universitas Hang Tuah, 2025)
Maritime safety is a fundamental aspect of the maritime industry that heavily relies on the competence and preparedness of the crew in dealing with emergency situations. The International Convention on Standards of Training, Certification, and Watchkeeping for Seafarers (STCW) establishes a safety training framework that must be met by every crew member worldwide. This research aims to highlight the urgency of STCW-based safety training, evaluate the effectiveness of its implementation, and identify the challenges faced in its execution on the ground. The methods used include literature review and descriptive analysis of training standards as well as case studies from several maritime incidents. The study results show that STCW-based safety training significantly improves the readiness of crew members to handle emergencies, reduces the risk of accidents, and strengthens the safety culture onboard. However, there are obstacles in the implementation of the training, such as disparities in facilities, limitations in trainer resources, and differences in compliance levels between countries. Therefore, stricter supervision, improvement in training quality, and harmonization of implementation standards at the global level are required.